The Negative Impact of Renewable Energy Consumption on Carbon Dioxide Emissions: An empirical evidence from South American Countries - Koengkan, Matheus; Fuinhas, José Alberto (Revista Brasileira de Energias Renováveis, 2017)
The impact of renewable energy consumption on the carbon dioxide emissions was analyzed for a panel of ten South American countries in a period from 1980 to 2012. The Autoregressive r to decompose the total effect of renewable energy consumption on the carbon dioxide emissions in its short- and long-run components. The results indicate that the consumption of renewable energy reduce the carbon dioxide emissions in -0.0420 % when the consumption of alternative sources increases in 1% in short-run. Keywords: Renewable energy, environmental, energy economics, econometric.